The use of mental imagery to improve sporting performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Fowler, Philip (Massey University, 2000)
The purpose of this study was to examine the effect of mental imagery training on the serving performance of elite junior tennis players. A multiple baseline across subjects design was utilised. Four junior tennis players from the Wellington Regional Tennis elite training programme carried out 29 trials in which twenty serves were observed for accuracy. Baseline measures of tennis serving accuracy were obtained. Consistent with a multiple baseline design, the intervention was introduced at different times for each subject. The baseline measures of tennis serving accuracy were then compared with tennis serving accuracy following the mental imagery intervention. Serving accuracy was then plotted for each trial and subjects' graphs were visually inspected for intervention related change against the baseline performance level. A significant improvement in tennis serving accuracy following intervention was demonstrated for all subjects by statistically significant t-tests (p<0.05). These results supported the experimental hypothesis that mental imagery training would be effective in improving physical performance of elite junior tennis players. It addition to its usefulness in improving physical performance, mental imagery has the advantages of having no risk of injury and is able to be employed outside of normal practice sessions.
Keywords: Tennis; Psychological aspects